Organızatıon and Conduct of the Scıentıfıc and Competıtıon Scıentıfıc and Technıcal Creatıvıty of Students - Egamnazarov Gairat Gaybullaevich, Tagaev Khuzhamberdi, Gapparov Behzod Nematillaevich, Turabov Anvar Mavlankulovich, (International Journal of Advanced Science and Technology, 2020)
The pedagogical possibilities and the methodology for evaluating the participants of the competition are presented on the example of scientific and technical creativity of students.Competitions of creative works of students in higher educational institutions have become an integral part of the educational process, a fruitful form of work of teams of teachers on the ideological and political education of students, youth, the formation of their worldview, increase educational and social activity.Indeed, correctly and qualitatively held review contests contribute to solving the following problems: increasing and deepening the professional interest of students in the study of special disciplines; identification of advanced and lagging teams, the organization of work on the scientific and technical creativity of students; improving the efficiency and quality of extracurricular activities in majors, increasing the number of students who are purposefully engaged in scientific research in subject and special circles, etc.Contests on scientific and technical creativity of students tell a great educational impact on the teaching staff. They constantly stimulate the activities of teachers and masters of industrial training in improving theoretical and methodological training, equip them with the skills and educational work with students.Based on this, in this paper, general recommendations are formulated on organizing the composition of the organizing committee and the job responsibilities of the jury members, as well as an assessment of the creative work submitted to the NTTS review contest.